Road Restraint Systems as a Basis for Roadside Safety Improvement. Issue 6 (February 2019) - Budzyński, Marcin; Gobis, Anna; Jamroz, Kazimierz; Jelinski, Lukasz; Ostrowski, Krzysztof
Abstract: Roadside-related crashes occur when vehicles run off the road. The majority of the crashes have severe outcomes, especially when an object is hit (tree, pole, supports, front wall of a culvert, barrier). These accidents represent app. 19% of all of Poland's road deaths. Roadside crashes involve: hitting a tree, hitting a barrier, hitting a sign or utility pole, vehicle roll-over on the roadside, vehicle roll-over on a slope and vehicle roll-over into a ditch. Understanding the effects of roadside factors on road safety requires in-depth research. The problem was partly addressed at the WMCAUS conference in 2017 [1]. Key to understanding the needs and tools of road infrastructure management for preventing run-off-road crashes or minimising their consequences is to identify the hazards and sources of hazards caused by wrong or improper use of road safety devices. It is also important to identify errors in the design, structure, construction and operation of road safety devices. Studying such an extended scope of the problem required fieldwork. Site tests had to be conducted such as hitting a wire rope barrier and a steel barrier on curve (test TB32), light and heavy vehicles hitting a bridge parapet (tests TB11 and TB51), hitting a transition between a steel and wire rope barrier (TB32) and crashes into a lighting column placed within the barrier's working width. In addition, the project includes numerical tests validated on the basis of site tests. This helps to assess the behaviour of road restraint systems when selected parameters are changed. The work is part of the RID Programme (Development of Road Innovation) and the RoSE project (Road Safety Equipment). In the article the authors present the effects of building a road restraint system database for a selected test site (about 3, 000 km of Poland's national roads). An outline of new road restraint system guidelines could only be developed after understanding the effects of restraint systems, the design, additional elements, type of road and safety barrier location on a road or engineering structure and the road and traffic conditions on their functionality and safety. The paper will present the preliminary results of this research. Once complete, the research will offer tools to help with the implementation of road restraint systems. The tools will ensure that road infrastructure is safer and that the most common mistakes are eliminated.